ANALISIS KEMAMPUAN NUMERASI ANAK USIA 4 – 5 TAHUN DI TK PERTIWI 27 GAJAHMUNGKUR KOTA SEMARANG - Sukat; Ida Dwijayanti; Sumarno (STKIP Subang, 2024)
Numeracy skills are the basis for understanding mathematics. Children who have a basic understanding of numbers, counting, and basic mathematical relationships will be better prepared to understand more complex mathematical concepts in the future. This research aims to analyze the numeracy abilities of children aged 4 - 5 years at Kindergarten Pertiwi 27 Gajahmungkur, Semarang City. The type of research used by researchers is descriptive quantitative. The population in the study were 10 children aged 4-5 years in Class A of Kindergarten Pertiwi 27 Gajahmungkur. The data collection technique used is observation. Based on the results of research conducted by researchers, it can be concluded that the final achievement was only 27.5% of the 10 children. Based on these values, it can be said that the numeracy abilities of children aged 4 - 5 years at Kindergarten Pertiwi 27 Gajahmungkur Semarang are in the beginning to develop category.